Seasonal Viral Loop Dynamics in Two Large Ultraoligotrophic Antarctic Freshwater Lakes - Sawstrom, C; Anesio, AM; Graneli, W; Laybourn-Parry, J (2007)
The effect of viruses on the microbial loop, with particular emphasis on bacteria, was investigated over an annual cycle in 2003-2004 in Lake Druzhby and Crooked Lake, two large ultraoligotrophic freshwater lakes in the Vestfold Hills, Eastern Antarctica. Viral abundance ranged from 0.16 to 1.56 109 particles _1 and bacterial abundances ranged from 0.10 to 0.24 109 cells _1, with the lowest bacterial abundances noted in the winter months. Virus-to-bacteria ratios (VBR) were consistently low in both lakes throughout the season, ranging from 1.2 to 8.4. lysogenic bacteria, determined by induction with mitomycin C, were detected on three sampling occasions out of 10 in both lakes. In Lake Druzhby and Crooked Lake, lysogenic bacteria made up between 18% and 73% of the total bacteria population during the lysogenic events. Bacterial production ranged from 8.2 to 304.9 106 cells _1 day _1 and lytic viral production ranged from 47.5 to 718.4 106 viruslike particles _1 day _1. When only considering primary production, heterotrophic nanoflagellate (HNF) grazing and viral lysis as the major contributors to the DOC pool (i.e., autochthonous sources), we estimated a high contribution from viruses during the winter months when 960% of the carbon supplied to the DOC pool originated from viral lysis. In contrast, during the summer G20% originated from viral lysis. Our study shows that viral process in ultraoligotrophic Antarctic lakes may be of quantitative significance with respect to carbon flow especially during the dark winter period.